Aerogel materials for insulation in buildings - Yu, C; Fu, Q; Tsang, S (Elsevier, 2010)
Aerogel materials have recently received much attention since they give many exciting applications in a wide range of areas. This chapter highlights the processing of these materials, the resulting physicochemical properties and their applications. Thus, fundamental understandings in the techniques for processing of aerogel materials including conventional drying, supercritical drying, freeze-drying, ambient-pressure drying with regards to material density and void size distribution, thermal conductivity, optical and acoustic properties are provided. In addition, a number of chemical post-treatments for surface engineering of aerogel materials are included. Finally, potentially new applications of using these materials as thermal insulation for building, optical sensor, space dust collector and catalysis are discussed. © 2010 Woodhead Publishing Limited All rights reserved.